2014
DOI: 10.3390/cli3010001
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Groundwater Levels and Recharge Patterns in Northern Ghana

Abstract: Evaluating groundwater levels and recharge patterns is part of sustainably managing the water supply and predicting the possibility of water shortages, especially in light of climate change, extreme events (floods/droughts), increasing population and development. In the northern region of Ghana, groundwater is increasingly relied upon as a source of potable water for rural populations, but seasonal and inter-annual fluctuations of groundwater levels and recharge patterns are not always known. The fluctuation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…So, the lower the location of soil in topohydrosequence, the smaller the impact of precipitation from the previous year on the mean annual water table depth. Lutz et al [5] and Liang et al [42] have reported that it is difficult to find a direct relationship between precipitation and the groundwater level because of the complex factors determining the groundwater depth. In our study low values of the regression coefficient were obtained taking into account the relationship between precipitation and water table depth only.…”
Section: Resultsmentioning
confidence: 99%
“…So, the lower the location of soil in topohydrosequence, the smaller the impact of precipitation from the previous year on the mean annual water table depth. Lutz et al [5] and Liang et al [42] have reported that it is difficult to find a direct relationship between precipitation and the groundwater level because of the complex factors determining the groundwater depth. In our study low values of the regression coefficient were obtained taking into account the relationship between precipitation and water table depth only.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have assessed the availability of groundwater resources based on the estimation of groundwater recharge and draft with various techniques in different countries, i.e. Mexico (Scott and Shah, 2004), Turkey (Gundogdu and Guney, 2007;Aksever et al, 2015), USA (Harou and Lund, 2008), Ghana (Lutz et al, 2015), China (Wang and Zhao, 2015), India (Scott and Shah, 2004;Kumar and Remadevi, 2006;Bhuiyan et al, 2009;Reddy, 2012;Surinaidu et al, 2012;Lakshmamma et al, 2015) and Bangladesh (Jahan et al, 2010;Shahid et al, 2015). In this study, we also discussed the results of groundwater recharge and draft in Jodhpur district of Rajasthan, India along with the rainfall pattern.…”
Section: Resultsmentioning
confidence: 93%
“…However, few studies have been conducted to show how the groundwater level reacted to climate variability. The few studies that have addressed the issue [29][30][31] have faced a lack of data and have struggled to apply appropriate methods. These kinds of analyses require that further studies be conducted with other methods.…”
Section: Introductionmentioning
confidence: 99%